PARENTS — THE JEWEL OF OUR LIVES AND THE FOUNDATION OF OUR HAPPINESS - Jaloliddinova Guliraʻno Dilmurod qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article, written from the perspective of a 6th grade student from Uzbekistan, reflects on the immeasurable value of parents in a child’s life. Through heartfelt observations and cultural wisdom, the author explores the distinct yet complementary roles of a father and a mother, and underlines the sacred duty of children to honour, respect, and cherish their parents throughout their lives. The article serves as a sincere reminder that parents are the greatest treasure a person can ever possess.